S100A9 Derived from Chemoembolization‐Induced Hypoxia Governs Mitochondrial Function in Hepatocellular Carcinoma Progression. Issue 30 (30th August 2022) - Zhong, Chengrui; Niu, Yi; Liu, Wenwu; Yuan, Yichuan; Li, Kai; Shi, Yunxing; Qiu, Zhiyu; Li, Keren; Lin, Zhu; Huang, Zhenkun; Zuo, Dinglan; Yang, Zhiwen; et al.
Abstract: Transarterial chemoembolization (TACE) is the major treatment for advanced hepatocellular carcinoma (HCC), but it may cause hypoxic environment, leading to rapid progression after treatment. Here, using high‐throughput sequencing on different models, S100 calcium binding protein A9 (S100A9) is identified as a key oncogene involved in post‐TACE progression. Depletion or pharmacologic inhibition of S100A9 significantly dampens the growth and metastatic ability of HCC. Mechanistically, TACE induces S100A9 via hypoxia‐inducible factor 1α (HIF1A)‐mediated pathway. S100A9 acts as a scaffold recruiting ubiquitin specific peptidase 10 and phosphoglycerate mutase family member 5 (PGAM5) to form a tripolymer, causing the deubiquitination and stabilization of PGAM5, leading to mitochondrial fission and reactive oxygen species production, thereby promoting the growth and metastasis of HCC. Higher S100A9 level in HCC tissue or in serum predicts a worse outcome for HCC patients. Collectively, this study identifies S100A9 as a key driver for post‐TACE HCC progression. Targeting S100A9 may be a promising therapeutic strategy for HCC patients. Abstract : S100 calcium binding protein‐A9 (S100A9) is associated with post‐transarterial chemoembolization (TACE) hepatocellular carcinoma (HCC) progression. TACE increases the expression of S100A9 in HCC cells. S100A9 promotes binding between ubiquitin specific peptidase‐10 (USP10) and phosphoglycerate mutase family member‐5 (PGAM5), leading to the stabilization of PGAM5, which increases reactive oxygen species levels and subsequently inducing the growth and metastasis of HCC.